2010
DOI: 10.1098/rsbl.2010.0348
|View full text |Cite
|
Sign up to set email alerts
|

Is group size related to longevity in mammals?

Abstract: Life-history theory predicts that reduced extrinsic risk of mortality should increase species longevity over evolutionary time. Increasing group size should reduce an individual's risk of predation, and consequently reduce its extrinsic risk of mortality. Therefore, we should expect a relationship between group size and maximum longevity across species, while controlling for well-known correlates of longevity. We tested this hypothesis using a dataset of 253 mammal species and phylogenetic comparative methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
(39 reference statements)
0
33
2
Order By: Relevance
“…marmots [50] and Siberian jays [51]). There is also no association between cooperative breeding and species differences in age of first reproduction or longevity, and a previous study between longevity and group size also suggested that differences in the pace of life are not linked to the evolution of sociality in mammals [52].…”
Section: Discussionmentioning
confidence: 92%
“…marmots [50] and Siberian jays [51]). There is also no association between cooperative breeding and species differences in age of first reproduction or longevity, and a previous study between longevity and group size also suggested that differences in the pace of life are not linked to the evolution of sociality in mammals [52].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, body size differences can indicate differences in life history (see Vitone et al 2004;Webster et al 2004;Møller 2006b;Kamilar et al 2010), which may also involve factors that influence the probability of sampling. Accordingly, body mass was recorded as the mean mass of males and females from the breeding season, as reported by Cramp andPerrins (1977-1994).…”
Section: Biological Predictorsmentioning
confidence: 99%
“…Intraspecific variation in primates has since been examined at several different levels of analysis, including among age/sex classes, across seasons or generations (temporal) within a single site, among groups within a single site, and among sites or populations (geographic) ( Table 1). However, despite its importance to understanding broad-scale patterns of diversity, studies examining intraspecific variation in primate behavior and ecology are comparatively sparse (Foster and Endler 1999;Kappeler et al 2013), and the large majority of comparative studies have continued to focus on species' norms (e.g., mean values) at the interspecific level (Clutton-Brock and Harvey 1977;Terborgh 1983;Sterck et al 1997;Lee 1999;Nunn 1999;Kamilar et al 2010).…”
Section: Communicated By E Huchardmentioning
confidence: 99%
“…The WorldClim database has been frequently used in comparative ecology studies to quantify abiotic conditions and, therefore, as a proxy for habitat characteristics (e.g., Graham et al 2012;Kamilar et al 2012;Kamilar and Beaudrot 2013). Furthermore, these data have been well correlated with habitat types on the ground (e.g., Kamilar et al 2010). The climate data were extracted for the geographic location of each site using ArcGIS 9.0.…”
Section: Predictors Of Social Organization Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation